Nonsexual Transmission of Anogenital Warts in Children: A Retrospective Analysis - Valerie Jones; Shawn J. Smith; Hatim A. Omar (The Scientific World Journal)
The purpose was to evaluate the prevalence of sexual abuse in patients who were referred to a pediatric gynecologist for evaluation based on the clinical findings of anogenital warts. A retrospective analysis was performed on 131 patients between the ages 6 month and 9 years referred to a pediatric gynecologist after the finding of anogenital warts by a clinical provider, parent or caregiver. A complete physical examination under colposcopy by a the same, trained pediatric gynecologist was completed, and a complete medical and family history including maternal and sibling history for evidence of Human Papillomavirus (HPV) and anogenital warts. The legal system completed a full investigation to examine the sexual abuse allegations. In 131 patients with anogenital warts, a maternal history of warts, cervical dysplasia or both was present in 66 (50%). The remaining patients had either a negative maternal history for HPV clinical findings (54 patients or 41.2%), or maternal history was unknown (11 patients, or 8.3%). Of 131 patients, 81 (61%) patients had a sibling. Of those with siblings 40 (49.4%) had warts and 41 (50.6%) did not. Forty-five (34%) of the cases had a positive maternal history for warts, dysplasia or both but also had a sibling. In that cohort, 32 (71%) of the siblings also had anogenital warts. Three of 131 patients were ruled suspicious for sexual abuse by the legal authorities but not confirmed. Of those three patients two were female and one was male. Two had no maternal history for HPV and both of these patients had a sibling without anogenital warts. Most cases of anogenital warts in children are likely to be the result of non-sexual transmission, namely prenatal mode. Thus, these patients should be handled differently by the legal system unless other reasons for suspicion exist. This study also showed the importance of maternal gynecologic history.